Statistical reasoning and methods - Johnson, Richard Arnold; Tsui, Kam-Wah. (New York : Wiley, 1998)
About statistics. Organizing data and describing patterns. Describing bivariate data. Probability-the basis for inference. Random variables and probability distributions. Normal distribuitons. Variation in repeated samples-sampling distributions...
Includes index.
Keywords: Mathemetics; Mathematical statistics; Mathematical statistics